CYT387 Inhibits the Hyperproliferative Potential of Fibroblast-like Synoviocytes via Modulation of IL-6/JAK1/STAT3 Signaling in Rheumatoid Arthritis. (18th August 2022) - Srivastava, Susmita; Samarpita, Snigdha; Ganesan, Ramamoorthi; Rasool, Mahaboobkhan
ABSTRACT: Fibroblast-like synoviocytes (FLS) are the critical effector cells primarily involved in rheumatoid arthritis (RA) disease pathogenesis. Interleukin (IL)-6, a proinflammatory cytokine most abundantly expressed in the rheumatoid synovium, promotes Janus kinase (JAK)/signal transducer and transcriptional activator (STAT) signaling cascade activation in RA-FLS, thus leading to its aggressive phenotype, invasiveness, and joint destruction. Momelotinib (CYT387) is a selective small-molecule inhibitor of JAK1/2 and is clinically approved to treat myelofibrosis. However, the therapeutic efficacy of CYT387 in FLS mediated RA pathogenesis is less known. In the present study, we investigated the modulatory effect of CYT387 on IL6/JAK/STAT signaling cascade in FLS induced RA pathogenesis. CYT387 treatment inhibited IL-6 induced high proliferative and migratory potential of FLS cells isolated from adjuvant-induced arthritic (AA) rats. CYT387 reduced the expression of PRMT5, survivin, and HIF-1α mediated by IL-6/sIL-6R in AA-FLS in a dose-dependent manner. The IL-6/sIL-6R induced expression of angiogenic factors such as VEGF and PIGF in AA-FLS cells was found downregulated by CYT387 treatment. Importantly, CYT387 significantly reduced IL-6/sIL-6R dependent activation of JAK1 and STAT3 and increased SOCS3 expression in AA-FLS cells. Next, the S3I-201 mediated blockade of STAT3 activation supported the inhibitory effect of CYT387 on IL-6/JAK1/STAT3 signaling cascade in AA-FLS. Overall, this study proves that CYT387 inhibits proliferation, migration, and pathogenic disease potential of FLS isolated from adjuvant-induced arthritic (AA) rats via targeting IL-6/JAK1/STAT3 signaling cascade.